THE EXPERIENCE OF CREATING SPECIALIZED VIRTUAL RESEARCH COMMUNITIES (EXAMPLE OF THE NETWORK OF IDENTITY RESEARCH) - Nazukina, M.V. (Perm Federal Research Centre Journal, 2015)
The article considers the experience of using online communities for research purposes. The activities of the Expert Network in identity research are analysed.